2018
DOI: 10.1007/s10509-018-3313-2
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi-V string cosmological model with dark energy anisotropy

Abstract: The role of anisotropic components on the dark energy and the dynamics of the universe is investigated. An anisotropic dark energy fluid with different pressures along different spatial directions is assumed to incorporate the effect of anisotropy. One dimensional cosmic strings aligned along x-direction supplement some kind of anisotropy. Anisotropy in the dark energy pressure is found to evolve with cosmic expansion at least at late times. At an early phase, the anisotropic effect due to the cosmic strings s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The Bianchi type (BT) models are the nice and simplest anisotropic models, which completely explain the anisotropic effects. Mishra et al [59] have investigated BT-V string cosmological model with anisotropic distribution of DE. Aditya and Reddy [60] have studied BT-I string models in modified theory of gravity.…”
Section: (): V-volmentioning
confidence: 99%
“…The Bianchi type (BT) models are the nice and simplest anisotropic models, which completely explain the anisotropic effects. Mishra et al [59] have investigated BT-V string cosmological model with anisotropic distribution of DE. Aditya and Reddy [60] have studied BT-I string models in modified theory of gravity.…”
Section: (): V-volmentioning
confidence: 99%
“…Mishra et al. [ 12 ] have found the anisotropy in the dark energy pressure that have evolved at late time. The cosmological models in a non‐interacting two fluid scenario such as the usual dark energy and electromagnetic field have been studied and have shown the dominance of dark energy at the late time of the evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [24][25][26] also investigated cosmological models with hybrid expansion which stimulates the cosmic transition from deceleration to acceleration epoch. In order to obtain a generalized hybrid universe, we consider a generalized hybrid scale factor of the universe in the form [28,29]…”
Section: Model With Generalized Hybrid Expansion Lawmentioning
confidence: 99%
“…From the WMAP data [23], it is revealed that the standard cosmological model requires positive and dynamic cosmological parameters that resemble the Bianchi universe. Mishra et al [24][25][26] also investigated cosmological models with hybrid expansion law which produce a time-varying deceleration parameter that stimulates the cosmic transition.…”
Section: Introductionmentioning
confidence: 99%